PENGARUH KUALITAS PELAYAN DAN HARGA TERHADAP LOYALITAS PELANGGAN DI BOLLY DEPT STORE TENTE - alif ansyari; Irma Mardian (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine the quality of service and price on customer loyalty at the Bolly Department Store Tente. The approach used in this research is using an associative approach. The population in the study were people who shopped more than twice with a sample of 96 people. Data collection techniques used are observation, questionnaires, and literature study. The data analysis techniques used were validity and reliability tests, classical assumption tests, multiple linear using regression analysis, correlation coefficients, coefficients of determination, T tests, and F tests by processing the Statistical Product and Service Solution (SPSS) version 23 program. The results showed that Service Quality (X1) has a significant effect on Loyalty. Price (X2) has a significant effect on Loyalty. And Service Quality (X1) and Price (X2) simultaneously (simultaneously) have a significant effect on Loyalty at the Bolly Dept. Store Tente.